Explosive solutions of elliptic equation with singular weight. Issue 8 (11th June 2021) - Wang, Ying
Abstract : Some instances of explosive solution to elliptic equation of the form Δ u = b ( x ) u p − d i s t ( x, ∂ Ω ) − q in a bounded smooth domain Ω ⊂ R N have been studied but only the case b is constant or b ∈ C ( Ω ¯ ) seem to have been considered up to now, at the best of our knowledge. In this paper, b is a positive weight function which can be singular on ∂ Ω . We obtain existence, uniqueness and exact boundary behaviour of positive solution.